Pharmacological Activities of Warm Alkaline Hydrogen Peroxide Solution and Therapeutic Potential in Medicine: Physical-Chemical Reprofiling as a Promising Lead for Drug Discovery - Urakova, Natalya; Urakov, Aleksandr; Shabanov, Petr (Anti-Infective Agents, 2025)
The traditional use of antiseptics, chemotherapeutic, expectorant, mucolytic drugs, and oxygen gas by artificial ventilation does not effectively eliminate hypoxemia in sputum, mucus, pus, and blood asphyxia in COVID-19. The emergency conversion of sputum, mucus, pus, and blood into oxygenated foam inside the airways utilizing the enzyme catalase and warm alkaline hydrogen solutions (WAHPSs) is proposed as a promising area for new therapeutic development. The possibility of physical-chemical repurposing of hydrogen peroxide from an antiseptic in pyolytics, mucolytics, hemolytics, and oxygen-producing antihypoxants by converting a cold, acidic non-carbonated drug into an oxygen-saturated WAHPS and its intrapulmonary injection is pointed out as a way to solve this problem. The possibility of medically enriching blood oxygen in hypoxemia by catalase cleavage of hydrogen peroxide when WAHPSs are administered orally as energy drinks or directly into the blood as injections is pointed out. The fact is that virtually all human tissues are rich in catalase, which immediately breaks down hydrogen peroxide into water and oxygen gas. Inhalation and/or intrapulmonary injections of WAHPSs have been shown to provide intra-airway interaction with catalase in sputum, mucus, pus and/or blood and releases oxygen gas, which foams the biological masses, is absorbed into the blood and eliminates hypoxemia. Thus, the physical-chemical repurposing of known drugs can be considered a promising direction for the discovery of new drugs.Value of the data:1) Why are these data useful?These studies indicate that the enzyme catalase, which is present in many tissues of animals and humans in both normal and disease, can be employed to enrich the tissues with oxygen and eradicate hypoxia when hydrogen peroxide solution is injected into them.2) Who can benefit from these data?Mountaineers, divers, submarine sailors, miners, astronauts, traumatologists, resuscitators, cardiologists, transplantologists, pulmonologists, obstetricians and gynecologists, emergency physicians, EMERCOM personnel, and medical workers, providing emergency medical care in cases of smoke in rooms, lack of oxygen in the inhaled air, drowning, bronchial asthma attack, acute respiratory distress syndrome, and asphyxia can use the data presented in this article.3) How can these data be used/reused for further insights or development of experiments?These data can be used to develop new antihypoxants, to improve methods of increasing the organism's endurance to hypoxia, methods of organ and tissue preservation, methods of ischemia treatment, methods of emergency medical care in urgent conditions, methods of ARDS treatment and standards of medical care.
Keywords: hypoxia